First pass effect in patients with large vessel occlusion strokes undergoing neurothrombectomy: insights from the Trevo Retriever Registry - Jadhav, Ashutosh P; Desai, Shashvat M; Budzik, Ronald F; Gupta, Rishi; Baxter, Blaise; English, Joey D; Bartolini, Bruno Mario; Krajina, Antonin; Haussen, Diogo C; Nogueira, Raul G; Liebeskind, David; Veznedaroglu, Erol (Journal of neurointerventional surgery, 2021)
BACKGROUND: First pass effect (FPE), defined as near-total/total reperfusion of the territory (modified Thrombolysis in Cerebral Infarction (mTICI) 2c/3) of the occluded artery after a single thrombectomy attempt (single pass), has been associated with superior safety and efficacy outcomes than in patients not experiencing FPE. OBJECTIVE: To characterize the clinical features, incidence, and predictors of FPE in the anterior and posterior circulation among patients enrolled in the Trevo Registry. METHODS: Data were analyzed from the Trevo Retriever Registry. Univariate and multivariable analyses were used to assess the relationship of patient (demographics, clinical, occlusion location, collateral grade, Alberta Stroke Program Early CT Score (ASPECTS)) and device/technique characteristics with FPE (mTICI 2c/3 after single pass). RESULTS: FPE was achieved in 27.8% (378/1358) of patients undergoing anterior large vessel occlusion (LVO) thrombectomy. Multivariable regression analysis identified American Society of Interventional and Therapeutic Neuroradiology (ASITN) levels 2-4, higher ASPECTS, and presence of atrial fibrillation as independent predictors of FPE in anterior LVO thrombectomy. Rates of modified Rankin Scale (mRS) score 0-2 at 90 days were higher (63.9% vs 53.5%, p<0.0006), and 90-day mortality (11.4% vs 12.8%, p=0.49) was comparable in the FPE group and non-FPE group. Rate of FPE was 23.8% (19/80) among basilar artery occlusion strokes, and outcomes were similar between FPE and non-FPE groups (mRS score 0-2, 47.4% vs 52.5%, p=0.70; mortality 26.3% vs 18.0%, p=0.43). Notably, there were no difference in outcomes in FPE versus non-FPE mTICI 2c/3 patients. CONCLUSION: Twenty-eight percent of patients undergoing anterior LVO thrombectomy and 24% of patients undergoing basilar artery occlusion thrombectomy experience FPE. Independent predictors of FPE in anterior circulation LVO thrombectomy include higher ASITN levels, higher ASPECTS, and the presence of atrial fibrillation.
Keywords: cerebrovaskulární poruchy; Prospective Studies; senioři nad 80 let; trombektomie; Humans; lidé středního věku; prospektivní studie; Aged, 80 and over; Middle Aged; ischemická cévní mozková příhoda; Registries; Brain Ischemia; Ischemic Stroke; mužské pohlaví; výsledek terapie; Treatment Outcome; ischemie mozku; registrace; ženské pohlaví; lidé; Aged; senioři; Male; Thrombectomy; Cerebrovascular Disorders; Female